Decontamination of poultry feed from ochratoxin A by UV and sunlight radiations. (28th September 2015) - Ameer Sumbal, Gul; Hussain Shar, Zahid; Hussain Sherazi, Syed Tufail; Sirajuddin,; Nizamani, Shafi Muhammad; Mahesar, Safaraz Ahmed
Abstract: BACKGROUND: Mycotoxin‐contaminated feed is very dangerous for the growth and even life of poultry. The objective of the current study was to investigate the efficacy of ultra‐violet irradiation for decontamination of ochratoxin A (OTA) in spiked and naturally contaminated poultry feed samples. Spiked and naturally contaminated feed samples were irradiated with ultra‐violet light (UV) at distance of 25 cm over the feed samples. In vitro, the effect of UV intensity (0.1 mW cm −2 at 254 nm UV‐C) on different types of poultry feeds contaminated with OTA was evaluated. The same samples were also irradiated with sunlight and analysed for OTA by an indirect enzyme linked immunosorbent assay method. RESULTS: Poultry feed samples containing 500 µg kg −1 were 100% decontaminated in 180 min with UV radiation while OTA was decreased to 70–95 µg kg −1 using the same poultry feed samples after 8 h sunlight irradiation. Therefore, UV light was found to be more effective. Only 1 h of UV irradiation was found to be sufficient to bring the OTA level to the maximum regulatory limit suggested for poultry feeds (100 µg kg −1 ), while 8 h were needed to obtain this level using sunlight radiations. CONCLUSION: The proposed approach is a viable option to reduce the level of OTA in contaminated poultry feeds. © 2015 Society of Chemical Industry